S_β-Open Sets and S_β-Continuity in Topological Spaces: Alias B. Khalaf, Nehmat K. Ahmed - Team, Support (Thai Journal of Mathematics, 2013)
In this paper we introduce a subclass of semi open sets called S_β-open sets in topological spaces. This class of sets used to define and study the concept of S_β-continuous functions.